Increased IPM knowledge among Beninese farmers - Lund, T.; Saethre, M.G.; Nyborg, I.; Coulibaly, O.; Rahman, M.H. (2010)
This paper reports on a project to train Beninese vegetable producers in integrated production methods. The concept and design of the project 'Healthy Vegetables through Participatory Integrated Pest Management (IPM) in Peri-Urban Gardens of Benin' are discussed, as well as its impact, including increased IPM knowledge. Also discussed are the need for experiential learning, the factors hindering use of IPM, and the measures needed towards more effective IPM.